“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Electron–Nuclear Coherent Coupling and Nuclear Spin Readout through Optically Polarized VB– Spin States in hBN - Murzakhanov, Fadis F.; Mamin, Georgy Vladimirovich; Orlinskii, Sergei Borisovich; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur; Aharonovich, Igor; Gottscholl, Andreas; Sperlich, Andreas; Dyakonov, Vladimir; Soltamov, Victor A. (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Nonlinear Imaging of Nanoscale Topological Corner States - Kruk, Sergey S.; Gao, Wenlong; Choi, Duk-Yong; Zentgraf, Thomas; Zhang, Shuang; Kivshar, Yuri (Nano Letters)
Topological states of light represent counterintuitive optical modes localized at boundaries of finite-size optical structures that originate from the properties of the bulk. Being defined by bulk properties, such boundary states are insensitive to certain types of perturbations, thus naturally enhancing robustness of photonic circuitries. Conventionally, the N-dimensional bulk modes correspond to (N – 1)-dimensional boundary states. The higher-order bulk-boundary correspondence relates N-dimensional bulk to boundary states with dimensionality reduced by more than 1. A special interest lies in miniaturization of such higher-order topological states to the nanoscale. Here, we realize nanoscale topological corner states in metasurfaces with C6-symmetric honeycomb lattices. We directly observe nanoscale topology-empowered edge and corner localizations of light and enhancement of light–matter interactions via a nonlinear imaging technique. Control of light at the nanoscale empowered by topology may facilitate miniaturization and on-chip integration of classical and quantum photonic devices.

Spin Polarization, Electron–Phonon Coupling, and Zero-Phonon Line of the NV Center in 3C-SiC - Jurgen von Bardeleben, Hans; Cantin, Jean-Louis; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Nonlinear imaging with all-dielectric metasurfaces - Schlickriede, Christian; Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Kivshar, Yuri; Zentgraf, Thomas (Nano Letters)

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Silicon metasurfaces for third harmonic geometric phase manipulation and multiplexed holography - Reineke, Bernhard; Sain, Basudeb; Zhao, Ruizhe; Carletti, Luca; Liu, Bingyi; Huang, Lingling; de Angelis, Costantino; Zentgraf, Thomas (Nano Letters)

Simultaneous Spectral and Spatial Modulation for Color Printing and Holography Using All-dielectric Metasurfaces - Wei, Qunshuo; Sain, Basudeb; Wang, Yongtian; Reineke, Bernhard; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (Nano Letters)

Strong Nonlinear Optical Activity Induced by Lattice Surface Modes on Plasmonic Metasurface - Chen, Shumei; Reineke, Bernhard; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Fluoroethylene Carbonate Induces Ordered Electrolyte Interface on Silicon and Sapphire Surfaces as Revealed by Sum Frequency Generation Vibrational Spectroscopy and X-ray Reflectivity - Horowitz, Yonatan; Steinrück, Hans-Georg; Han, Hui-Ling; Cao, Chuntian; Abate, Iwnetim Iwnetu; Tsao, Yuchi; Toney, Michael F.; Somorjai, Gabor A. (Nano Letters)

The Role of Electronic and Phononic Excitation in the Optical Response of Monolayer WS2 after Ultrafast Excitation - Ruppert, Claudia; Chernikov, Alexey; Hill, Heather M.; Rigosi, Albert F.; Heinz, Tony F. (Nano Letters)
Transient changes of the optical response of WS2 monolayers are studied by femtosecond broadband pump–probe spectroscopy. Time-dependent absorption spectra are analyzed by tracking the line width broadening, bleaching, and energy shift of the main exciton resonance as a function of time delay after the excitation. Two main sources for the pump-induced changes of the optical response are identified. Specifically, we find an interplay between modifications induced by many-body interactions from photoexcited carriers and by the subsequent transfer of the excitation to the phonon system followed by cooling of the material through the heat transfer to the substrate.
Keywords: Atomically thin 2D materials; carrier and phonon dynamics; ultrafast spectroscopy

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

Ultrathin Nonlinear Metasurface for Optical Image Encoding - Walter, Felicitas; Li, Guixin; Meier, Cedrik; Zhang, Shuang; Zentgraf, Thomas (Nano Letters)

Nonlinear Metasurface for Simultaneous Control of Spin and Orbital Angular Momentum in Second Harmonic Generation - Li, Guixin; Wu, Lin; Li, King F.; Chen, Shumei; Schlickriede, Christian; Xu, Zhengji; Huang, Siya; Li, Wendi; Liu, Yanjun; Pun, Edwin Y. B.; Zentgraf, Thomas; Cheah, Kok W.; et al. (Nano Letters)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

In Situ Study of Silicon Electrode Lithiation with X-ray Reflectivity - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Stone, Kevin H.; Toney, Michael F. (Nano Letters)

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

Dispersionless Phase Discontinuities for Controlling Light Propagation - Huang, Lingling; Chen, Xianzhong; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

Compact Magnetic Antennas for Directional Excitation of Surface Plasmons - Liu, Yongmin; Palomba, Stefano; Park, Yongshik; Zentgraf, Thomas; Yin, Xiaobo; Zhang, Xiang (Nano Letters)

A Carpet Cloak for Visible Light - Gharghi, Majid; Gladden, Christopher; Zentgraf, Thomas; Liu, Yongmin; Yin, Xiaobo; Valentine, Jason; Zhang, Xiang (Nano Letters)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Transformational Plasmon Optics - Liu, Yongmin; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nano Letters)

Enhanced Sequential Carrier Capture into Individual Quantum Dots and Quantum Posts Controlled by Surface Acoustic Waves - Völk, Stefan; Schülein, Florian J. R.; Knall, Florian; Reuter, Dirk; Wieck, Andreas D.; Truong, Tuan A.; Kim, Hyochul; Petroff, Pierre M.; Wixforth, Achim; Krenner, Hubert J. (Nano Letters)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)